STRATEGI PENINGKATAN KINERJA DENGAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN ANALISIS STRENGTHS, OPPORTUNITIES, ASPIRATIONS, RESULTS (SOAR) - Suhartono Suhartono; Cita Rosari Putra (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
Bidkeu Polda D.I. Yogyakara as a work unit for financial development within the Kepolisian Daerah D.I. Yogyakarta is responsible for making the implementation of the financial administration process run smoothly, transparently, accountably and professionally. In order to support the implementation of the achievement of these goals, it is necessary to know the extent of the performance conditions and determine the strategy for improving the performance of the Bidang Keuangan Polda D.I. Financial Yogyakarta. Data analysis in this study used Importance Performance Analysis (IPA) and SOAR. IPA is an analyst by comparing the performance and level of expectations or interests of service recipients as an effort to improve the performance of the service provider organization. Furthermore, SOAR consists of four variables, namely S: Strength, O: Opportunity, A: Aspirations, R: Result. SOAR analysis comes from the Appreciative Inquiry (AI) approach, which is basically a strategy based on the positive things that a business or organization has to develop and make it its main advantage.Based on the results of research with IPA and SOAR, it is concluded that the strategy to improve the performance of the Bidang Keuangan Polda D.I. Financial Yogyakarta is a strategy: (1) Improving the quality of work results and timeliness of reporting. (2) Making efforts to add and maintain the facilities and infrastructure to office support . (3) Maintaining the friendliness of personnel in service. (4) Increasing the discipline of personnel working time. (5) Developing personnel potential. (6) Increase the work motivation of personnel. (7) Striving for the regeneration of Bidkeu Polda D.I. Yogyakarta.